The Impact of Contrast in Poeticizing a Text : An Interpretation of al-Mutanabby’s “ I Do Cherish You Should the Soul Be Taciturn” - Sulaiman , Buthayna; Ahmad , Al-Hadi (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
A text’s poetic characteristic is what gives it its literary attribute .The poetic characteristic of a structural constituent is what gives it the main attribute amongst others. Scholars, therefore, are interested ـــ when attempting to identify the poetic qualityــــ in tracing the technique, whose effective presence, along with its links to other set constituents, indicates that the studied text is distinguished for its poetic characteristic .Each artistic means, which is significant in indicating the implication of the text, is a poetic means. This is the paper’s hypothesis in illustrating the significance of contrast, relying upon a set of theoretical postulates, of which some are confined to linguistics, although they have their basis in Arab linguistic and rhetorical discourse. They help a scholar in drawing rhetorical conclusions, in the aftermath of examining the texts. As for the practical objective, the paper will try to make use of the theoretical postulates in dealing with one of al-Mutanabby’s texts, which are strikingly rich with contrasts: their abundance on the text's level. Thus , al-Mutanabby invested it [contrast] in weaving a network of relations linking the signified, whereby contrast is their main linking device, and the first controlling factor in directing them towards giving the text a consistent poetic structure.